Modulation of Spinal Nociceptive Transmission by Sub‐Sensory Threshold Spinal Cord Stimulation in Rats After Nerve Injury. Issue 1 (4th June 2019) - Yang, Fei; Duan, Wanru; Huang, Qian; Chen, Zhiyong; Ford, Neil; Gao, Xinyan; Sivanesan, Eellan; Sarma, Sridevi V.; Vera‐Portocarrero, Louis P.; Linderoth, Bengt; Raja, Srinivasa N.; Guan, Yun
Abstract : Objectives: High‐frequency spinal cord stimulation (SCS) administered below the sensory threshold (subparesthetic) can inhibit pain, but the mechanisms remain obscure. We examined how different SCS paradigms applied at intensities below the threshold of Aβ‐fiber activation (sub‐sensory threshold) affect spinal nociceptive transmission in rats after an L5 spinal nerve ligation (SNL). Materials and Methods: Electrophysiology was used to record local field potential (LFP) at L4 spinal cord before, during, and 0–60 min after SCS in SNL rats. LFP was evoked by high‐intensity paired‐pulse test stimulation (5 mA, 0.2 msec, 400 msec interval) at the sciatic nerve. Epidural SCS was delivered through a miniature electrode placed at T13‐L1 and L2‐L3 spinal levels. Four patterns of SCS (200 Hz, 1 msec; 500 Hz, 0.5 msec; 1200 Hz; 0.2 msec; 10, 000 Hz, 0.024 msec, 30 min, bipolar) were tested at 90% Aβ‐threshold as a subthreshold intensity. As a positive control, traditional SCS (50 Hz, 0.2 msec) was tested at 100% Aβ‐plateau as a suprathreshold intensity. Results: Traditional suprathreshold SCS at T13‐L1 level significantly reduced LFP to C‐fiber inputs (C‐LFP). Subthreshold SCS of 200 and 500 Hz, but not 1200 or 10, 000 Hz, also reduced C‐LFP, albeit to a lesser extent than did traditional SCS ( n = 7–10/group). When SCS was applied at the L2‐L3 level, only traditional SCS and subthreshold SCS of 200 Hz inhibited C‐LFP ( n = 8–10/group). Conclusions: Traditional suprathreshold SCS acutely inhibits spinal nociceptive transmission. Low‐frequency subthreshold SCS with a long pulse width (200 Hz, 1 msec), but not higher‐frequency SCS, also attenuates C‐LFP.